Jumlah Leukosit berkorelasi dengan Jumlah Trombosit pada Demam Tifoid Anak - Dian Nurmansyah; Lala Foresta Valentine Gunasari; Puspawati Puspawati; Maya Herliana Sasmitha (Media Ilmiah Kesehatan Indonesia, 2026)
Typhoid fever in children remains a health problem in developing countries, with hematological changes such as leukocyte and platelet abnormalities being frequently observed. This study aimed to analyze the relationship between leukocyte and platelet counts in pediatric patients with typhoid fever. A cross-sectional design was employed using secondary data from the Clinical Pathology Laboratory of RSDI Banjarbaru City. A total of 72 children aged 5–13 years who met the inclusion criteria (diagnosis of typhoid fever by Tubex TF, no prior antibiotic therapy) were analyzed. Leukocyte and platelet measurements were performed using a hematology analyzer, and data were analyzed using simple linear regression (SPSS version 24). Results showed a mean age of 8.2 years, with a higher proportion of males (59.7%). Leukocyte distribution was highly variable, ranging from severe leukopenia (1200–1248/mm³) to extremely high values. Platelet distribution was also wide, with very low values of 51,000/mm³ and high outliers up to 460,000/mm³. Regression analysis yielded the equation y = 13.74x + 118195 with a coefficient of determination (R²) of 0.4998, indicating that approximately 50% of the variability in platelet count could be explained by leukocyte count. Pathophysiologically, this relationship is mediated by proinflammatory cytokines (TNF-α, IL-1, IL-6) and leukocyte-platelet aggregation induced by Salmonella typhi endotoxin. In conclusion, there is a moderate positive correlation between leukocyte and platelet counts in children with typhoid fever. These hematological parameters have the potential to serve as adjunctive diagnostic tools and for risk stratification, particularly in settings with limited blood culture facilities.